Spatial topology in Singapore English: explorations in gesture forms and language universality - Ng, Yuan Jie (Nanyang Technological University, 2024)
Present-day investigations into spatial language have developed to a point of abstraction. Investigations capitalise on the breadth of research preceding them by opting to innovate at the post-hoc level; existing methods are thus truncated to derive presumed data primed for further research. As a result, the landscape of spatial language data is predominantly lexical themed. This study represents a pilot effort to broadly innovate spatial language investigation at the experimental level. A novel framework for analysing gesture as spatial language is inserted into an established research paradigm, and the results recorded to observe for potential patterns. Thirty participants were tasked to, in Singapore English, spatially encode eight scenes maximally representing topological space. Encodement forms at both verbal expression and physical gesture were recorded. Results showed that lexical spatial encodement patterns displays marginal differences at the varietal level, that gesture display their own range of encodement patterns delineated by participant idiosyncrasy, and that terms and gesture, while linked, featured minimal levels of encodement foci. This paper posits an initial study of spatial language at the intersection of lexicality and gesture–that while gesture and spatial language are salient markers of space, further research must be taken to unearth their correspondence.